LA CONSTITUCIÓN DE TRASTORNOS SEXUALES EN LA PSIQUIATRIA - Gamboa Barboza, Isabel (2011)
This research addresses the connection between the construction of identities, sexual behaviors, and medical practices. The article intends to analyze and understand the way in which medical approaches have a significant impact on the social labelling of the ill or those supposedly ill. The author analyzes how psychiatry –despite it no longer classifies homosexuality as a mental disease from a clinical viewpoint–continues to conceptualize some identities and sexual practices as disorders, taking as its key point of comparison or reference, certain identities or practices associated with reproductive heterosexuality as opposed to healthy sexual practices.